2017
DOI: 10.4103/pr.pr_52_17
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antiproliferative effect of earthworm coelomic fluid of Eudrilus eugeniae, Eisenia foetida, and Perionyx excavatus on squamous cell carcinoma-9 cell line: A pilot study

Abstract: Introduction:The earthworm coelomic fluid (ECF) has shown proven antiproliferative effect against breast, liver, gastrointestinal, and brain cancer, but it is least explored in oral cancer. The present in vitro study is an attempt to investigate the antiproliferative activity of ECF on oral cancer cell line squamous cell carcinoma (SCC)-9.Materials and Methods:ECF was collected from the species Eudrilus eugeniae (EE), Eisenia foetida (EF), and Perionyx excavatus (PE) stored at −80°C. Percentage inhibition of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Earthworm coelomic fluid and extracts showed antibacterial and antifungal activities (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) as well as antiviral action (18). Earthworm tissues, extracts, or isolated fractions and compounds exhibited anticancer activity toward different cancer cell lines (19)(20)(21)(22)(23)(24)(25)(26). The development of research on the antimicrobial activity in earthworms has gained momentum over the last few years, while the anticancer activity has been reported in few studies.…”
mentioning
confidence: 99%
“…Earthworm coelomic fluid and extracts showed antibacterial and antifungal activities (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) as well as antiviral action (18). Earthworm tissues, extracts, or isolated fractions and compounds exhibited anticancer activity toward different cancer cell lines (19)(20)(21)(22)(23)(24)(25)(26). The development of research on the antimicrobial activity in earthworms has gained momentum over the last few years, while the anticancer activity has been reported in few studies.…”
mentioning
confidence: 99%
“…Our results were also in accordance with Petelin's study, 13 that showed Reso-pac had only small inhibitory effects on fibroblast cell proliferation and found to be the most suitable dressing in comparison to Peri-pac, Barricaid and Fittydent, also same as other articles showed MTT assay was a reliable technique. [18][19][20]…”
Section: Discussionmentioning
confidence: 99%
“…It is currently clear that EMT has implications on cancer metastasis by triggering the loss of cell-cell adhesion to facilitate the invasion of cancer cell. However, the mechanism of RUNX3-mediated suppression of cancer metastasis remains unclear and the role of RUNX3 in colorectal cancer has not yet been well studied [11][12][13][14]. Further biochemical studies need to be followed up to investigate the mechanistic principles involved in RUNX3mediated inhibition of EMT in colitis associated colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Further biochemical studies need to be followed up to investigate the mechanistic principles involved in RUNX3mediated inhibition of EMT in colitis associated colon cancer. In the development of EMT, cancer cells lose the properties of epithelial cells and develop mesenchymal cell properties, including overexpression of vimentin [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation